IMPLEMENTATION OF CONTENT MASTERING SERVICES WITH THE MUJAHADAH APPROACH TO IMPROVING STUDENT DISCIPLINE: PELAKSANAAN LAYANAN PENGUASAAN KONTEN DENGAN PENDEKATAN MUJAHADAH TERHADAP PENINGKATAN DISIPLIN SISWA - Agung Prasetia (Institut Agama Islam Negeri Kerinci, Indonesia, 2021)
The research method used in this research is quantitative with the type of research experimental design One group Prettest and Posttest. In this study, the number of samples used was 40 students of class VIII at SMP N 1 Sungai Penuh. The instrument used in this study was the Student Discipline Scale and was processed using the paired t-test research method through the SPSS Version 25 application. The results showed that content mastery services with a mujahadah approach could have an effect on improving student discipline. This is indicated by the significance value (P) < 0.05 and Tcount > T table, with the calculation of the t-test results where the value of Sig, (2-tailed) < 0.005.